2023
DOI: 10.3390/ijerph20031659
|View full text |Cite
|
Sign up to set email alerts
|

Time to Play in Javanese Preschool Children—An Examination of Screen Time and Playtime before and during the COVID-19 Pandemic

Abstract: This comparative–descriptive multi-national research examined the screen time and playtime of preschool children aged 1–6 years before and during the COVID-19 pandemic. Parents reported on the play and screen habits of preschool-aged children on the weekday and weekends using a questionnaire on the lifestyle habits of their children. Results indicated a significant difference in screen time and playtime on the weekday and weekend before the pandemic (screen time: 1.91 ± 2.40 vs. 2.16 ± 2.60 h; playtime: 3.55 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…The recommendations regarding the 24-hours moving recommendations declared by one of them by Canada (Moore et al, 2020;Tremblay et al, 2016), the roots of the theory continue to spread to various countries in the world, not only multi-country studies in Europe (Kovacs et al, 2022), the mapping of the 24-hours recommendations have reached the continent of Asia, both in Japan (Hyunshik et al, 2021), Singapore (Chia et al, 2020), Australia (Cliff et al, 2017), and other countries. In Indonesia, studies in three major cities also concluded that there was a very significant increase in screen time when comparing before and during the pandemic (Nopembri et al, 2023), either in terms of the type of entertainment or no-show. When you increase screen time, it also correlates with decreased sleep and plays time (Fauziah et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendations regarding the 24-hours moving recommendations declared by one of them by Canada (Moore et al, 2020;Tremblay et al, 2016), the roots of the theory continue to spread to various countries in the world, not only multi-country studies in Europe (Kovacs et al, 2022), the mapping of the 24-hours recommendations have reached the continent of Asia, both in Japan (Hyunshik et al, 2021), Singapore (Chia et al, 2020), Australia (Cliff et al, 2017), and other countries. In Indonesia, studies in three major cities also concluded that there was a very significant increase in screen time when comparing before and during the pandemic (Nopembri et al, 2023), either in terms of the type of entertainment or no-show. When you increase screen time, it also correlates with decreased sleep and plays time (Fauziah et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The Covid-19 pandemic caused a crucial reduction in the need for physical education and the time involved in physical activity, so challenges were experienced by all teachers in schools (Pavlovic et al, 2021). The problem does not stop there, this is also related to taking other studies that show sedentary behavior that occurred before and during the pandemic, which investigated the behavior of decreased sleep time and increased time in front of the screen (Fauziah et al, 2022;Nopembri et al, 2023), followed by exploring the relationship between habit in front of the screen and decreased playing habits (Fauziah et al, 2022). Therefore, in order to prevent prolonged sedentary habits, it is necessary to initiate a new movement from the teacher in generating the desire to move, sweat, and socialize more actively than before.…”
Section: Introductionmentioning
confidence: 99%
“…Di Indonesia sendiri, penggunaan gadget pada anak usia dini mengalami peningkatan. Hasil penelitian dari Nopembri et. al (2023) menunjukan bahwa pada saat pandemi berlangsung, durasi penggunaan gadget pada anak usia dini mengalami peningkatan lebih dari dua kali lipat.…”
Section: Latar Belakangunclassified